Vacuum-assisted excision: a safe minimally invasive option for benign phyllodes tumor diagnosis and treatment—a systematic review and meta-analysis - Gil, Maria Luísa Braga Vieira; Coelho, Bertha Andrade; Couto, Henrique Lima; Silva, Henrique Moraes Salvador; Pessoa, Eduardo Carvalho; Sharma, Nisha; Mann, Ritse; McIntosh, Stuart A.; Diniz, Paulo Henrique Costa; Cantidio, Farley Soares; Gil, Gabriel Oliveira Bernardes; Salvador, Anna Dias; et al. (Frontiers in Oncology, 2024)
this is a systematic review and meta-analysis comparing surgical excision and percutaneous ultrasound-guided vacuum assisted excision (US-VAE) for treatment of benign phyllodes tumor (PT) using local recurrence (LR) as the endpoint.Objective: To determine the frequency of LR of benign PT after US-VAE compared to the frequency of LR after surgical excision.Method: Systematic review and meta-analysis (following the PRISMA standard) comparing LR in women older than 18 years old treated for benign PT by US-VAE compared with local surgical excision, with at least 12 months follow up. Studies were retrieved from PubMed, Scopus, Web of Science and Embase. The pooled effect measure used was the odds ratio (OR) of recurrence.Results: Five comparative prospective or retrospective observational studies published between 01/01/1992 and 01/10/2022, comparing surgical excision and percutaneous ultrasound-guided vacuum assisted excision (US-VAE) for local recurrence (LR) of benign phyllodes tumor (PT) met the selection criteria. Four were retrospective observational cohorts and one was a prospective observational cohort. In total 778 women were followed. Of these, 439 (56,4%) underwent local surgical excision and 339 (43,6%) patients had US-VAE. The median age of patients in the 5 studies ranged from 33,7 to 39 years old; the median size ranged from 1,5cm to 3,0cm and the median follow up ranged from 12 to 46,6 months. Needle gauge ranged from 7G to 11G. LR rates were not statically significant between US-VAE and surgical excision (41 of 339 versus 34 of 439; OR 1.3; p = 0.29).Conclusion: This meta-analysis suggests that using US-VAE for removal of benign PT does not increase local regional recurrence and is a safe minimally invasive therapeutic option.